Bank Capital and Loan Loss Reserves Under Basel II: Implications for Emerging Countries - Majnoni, Giovanni; Miller, Margaret; Powell, Andrew (World Bank, Washington, D.C., 2013)
The authors propose an integrated approach to minimum bank capital, and loan loss reserves regulation. They break new ground in two main areas. First, the authors provide an explicit measurement of the credit loss distribution for a sample of emerging countries, providing a benchmark for discussing the appropriate calibration of new regulatory capital, and loan loss provision requirements for non-G10 countries. Second, on normative grounds, they propose a simplified version of the "internal rating based" (IRB) approach as a transition tool that, while retaining a risk-based definition of solvency ratios, implies reduced supervisory monitoring costs, and could therefore be of interest to emerging countries, where supervisory resources are particularly scarce.